DN interaction from the Jülich meson-exchange model - Tolos, L.; Haidenbauer, J.; Krein, G. [UNESP] (AIP Publishing, 2012)
The DN interaction is studied in close analogy to the meson-exchange K̄N potential of the Jülich group using SU(4) symmetry constraints. The model generates the Λ c(2595) resonance dynamically as a DN quasi-bound state. Results for DN scattering lengths and cross sections are presented and compared with predictions based on the Weinberg-Tomozawa term. Some features of the Λ c(2595) resonance are also discussed emphasizing the role of the near-by πΣ c threshold. © 2012 American Institute of Physics.
Keywords: Λ c(2595) resonance; DN interaction; meson-exchange model